Quantitative titration of nucleic acids by enzymatic amplification reactions run to saturation. - Pannetier, C (1993)
In vitro enzymatic amplification of nucleic acids by PCR or other techniques is a very sensitive method to detect rare DNA segments. We present here a protocol that allows the rapid, sensitive and precise quantification of DNA molecules using PCR amplification run to saturation. The DNA (or cDNA) to be assayed is co-amplified with known amounts of an internal standard DNA. We show that the latter must be almost identical to the assayed DNA, otherwise quantification at the plateau is unreliable. The read-out of the amplification involves one or two additional oligonucleotides. Using fluorescent oligonucleotides as primers in run-off reactions together with an automated DNA sequencer, we could measure the level of expression of several genes, like the murine MHC class I H-2Kd or a specific T cell receptor beta chain transcript in the course of an immunization. mRNA levels were normalized by measuring in a similar manner the number of transcripts encoding the housekeeping gene HPRT. Finally, our procedure might allow the rapid analysis of a large number of samples at the same time, as illustrated by the simultaneous analysis of the mRNAs encoding the CD4 and CD8 murine T cell markers.